Thinking about your running movement makes you less efficient: attentional focus effects on running economy and kinematics - Schücker, L.; Parrington, L. (Journal of Sports Sciences, 2018)
A number of studies have shown that attentional focus instructions can effect running economy. This study assessed spiroergometry, as well as running kinematics as a possible mechanism to explain these effects. Twelve runners had to focus their attention on either their running movement, their breathing or on a video while running on a treadmill at a set, submaximum speed. Spiroergometry and running kinematics were measured. Results revealed worse running economy in both internal focus conditions (breathing and movement) compared to the external focus condition (video), replicating previous findings. In addition, vertical oscillation during the running movement was elevated in the movement compared to the video condition, indicating a less efficient running style. No changes in kinematics were found for the breathing compared to the video condition. Therefore, consciously focusing on the running movement moves runners away from their optimised running pattern and leads to detriments in economy. The decreases in running economy in the breathing condition can be better explained by changes in breathing patterns. Abstract fro author